2007
DOI: 10.2105/ajph.2006.088120
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Context on Changes in Fruit and Vegetable Consumption: Results of the Healthy Directions Studies

Abstract: As part of the Harvard Cancer Prevention Program Project, we used a social contextual model of health behavior change to test an intervention targeting multiple risk-related behaviors in working-class, multiethnic populations. We examined the relationships between the social contextual factors in our conceptual model and changes in fruit and vegetable consumption from baseline to completion of intervention in health centers and small business studies. We analyzed change in fruit and vegetable consumption, meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 67 publications
6
98
1
5
Order By: Relevance
“…An exception is Sorensen et al (2007), who evaluated an intervention which consisted of education and information in combination with environmental changes at workplaces. The results in Sorensen et al (2007) suggest that the intervention has a significantly greater impact on the dietary intake of females compared with males; a result that also finds support in our workplace survey, but not in the large-scale survey where no significant difference was found in the WTP between females and males.…”
Section: The Workplace Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…An exception is Sorensen et al (2007), who evaluated an intervention which consisted of education and information in combination with environmental changes at workplaces. The results in Sorensen et al (2007) suggest that the intervention has a significantly greater impact on the dietary intake of females compared with males; a result that also finds support in our workplace survey, but not in the large-scale survey where no significant difference was found in the WTP between females and males.…”
Section: The Workplace Surveymentioning
confidence: 99%
“…An exception is Sorensen et al (2007), who evaluated an intervention which consisted of education and information in combination with environmental changes at workplaces. The results in Sorensen et al (2007) suggest that the intervention has a significantly greater impact on the dietary intake of females compared with males; a result that also finds support in our workplace survey, but not in the large-scale survey where no significant difference was found in the WTP between females and males. The intervention in this study can also be seen as complement to the intervention in Lassen et al (2004), who evaluate an educational program for the canteen staff (in Danish firms) aimed at increasing the customers' intake of fruit and vegetables at lunch, where CTA also has the potential to improve the dietary intake of the employee's family.…”
Section: The Workplace Surveymentioning
confidence: 99%
“…18 It is a new instrument, used in the investigation of links between access to social capital and health care outcomes. 18,20 Associations between social capital and common types of mental illness, 2,12,19 depression, 6,20 self-reported health conditions, 7 fruit and vegetable consumption, 17 alcohol consumption and smoking, 5 obesity and diabetes, 8 and mortality rates for coronary disease 16 have already been found.…”
mentioning
confidence: 96%
“…For example, in one recent multiple health behavior change intervention focused on nutrition, gender was not associated with behavior change [11]. An important aspect of addressing the disparities in healthy lifestyle behaviors by occupational class [2, [4][5][6][7][8] is identifying appropriate intervention strategies for worksites that employ substantial proportions of men.…”
Section: Discussionmentioning
confidence: 99%
“…Disparities exist across US occupational classes and socioeconomic levels for meeting recommended goals for diet and physical activity; for example, blue-collar workers and people with lower socioeconomic position exhibit higher risk [2, [4][5][6][7][8]. While disparities in health behaviors across occupational class are well documented for discrete health behaviors [8], a few studies have also suggested that there may be disparities in clustering of health behaviors among people of different occupational classes and socioeconomic and education levels [9,10]. Since both chronic disease burden and clusters of unhealthy behaviors have been shown to be disproportionately high among blue-collar workers; examining contextually relevant programs that address multiple health behaviors is an important public health endeavor.…”
Section: Introductionmentioning
confidence: 99%